(m+7)(m-8)=

Simple and best practice solution for (m+7)(m-8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (m+7)(m-8)= equation:


Simplifying
(m + 7)(m + -8) = 0

Reorder the terms:
(7 + m)(m + -8) = 0

Reorder the terms:
(7 + m)(-8 + m) = 0

Multiply (7 + m) * (-8 + m)
(7(-8 + m) + m(-8 + m)) = 0
((-8 * 7 + m * 7) + m(-8 + m)) = 0
((-56 + 7m) + m(-8 + m)) = 0
(-56 + 7m + (-8 * m + m * m)) = 0
(-56 + 7m + (-8m + m2)) = 0

Combine like terms: 7m + -8m = -1m
(-56 + -1m + m2) = 0

Solving
-56 + -1m + m2 = 0

Solving for variable 'm'.

Factor a trinomial.
(-7 + -1m)(8 + -1m) = 0

Subproblem 1

Set the factor '(-7 + -1m)' equal to zero and attempt to solve: Simplifying -7 + -1m = 0 Solving -7 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1m = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1m = 0 + 7 -1m = 0 + 7 Combine like terms: 0 + 7 = 7 -1m = 7 Divide each side by '-1'. m = -7 Simplifying m = -7

Subproblem 2

Set the factor '(8 + -1m)' equal to zero and attempt to solve: Simplifying 8 + -1m = 0 Solving 8 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1m = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1m = 0 + -8 -1m = 0 + -8 Combine like terms: 0 + -8 = -8 -1m = -8 Divide each side by '-1'. m = 8 Simplifying m = 8

Solution

m = {-7, 8}

See similar equations:

| x-.24=465.12 | | 8m+19=-10 | | Log(9-4c)=2.5 | | -7p+2(-3p+2)=4(p+1) | | P=8n+4 | | 0.5/2a/3 | | 18=1-8p+1 | | 4+3n-8n=-3n-8+n+6 | | 8+6(6+6m)=116 | | 3h-1=5 | | 18-3n=4n+11 | | 13+8m=7m+14 | | w+15=2 | | 1-7y=2y-14 | | (2x)(x+4)=0 | | 5t+4r+9=0 | | 9+3.5f=11-0.5g | | 36+2y=-4y | | 5x+9-3x=0 | | X^2-4x-k+4=0 | | x+73=4961 | | 29-y=37 | | 5x+9=11x-27 | | (x)(4x+5)=520 | | 2y=-3x+29 | | -7x+9=19-3x | | -2y-3y+9=4-3-y | | 600=300+10c | | X^2-12x+49=22 | | 13y+2=9y+22 | | 97b=2037 | | 14x-9x=7 |

Equations solver categories